(3bWH GdYGQajfs - (3YHO GdQMef Hf jhSa Hf YHO GdQMef GdHLGFj,J (B599 (3g` s
(3ChdgG (B:s
(3CeG HYO jG CNj abO EfUQaJ geJi dhVY gPG GdcJGH hSejJ GdcJGH bWH GdYGQajf s
(3BNQgG (B:s
(3hbO hVYJ dgPG CjgG GdCN bWHkG ced bWH GdYGQajf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B342s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B- (3GdeZQH (B(186) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs